The Effect of Tobacco Extract (Nicotiana Tobacum) As a Anesthetic Material Against Hematological Conditions Gold Fish (Cyprinus Corpio) With Method Dry Transport - Rabiatun Abi Adamiah; Nunik Cokrowati; Alis Mukhlis (Jurnal Media Akuakultur Indonesia, 2023)
The need for carp (Cyprinus carpio) from year to year continues to increase with the increase in population. Consumer demand for fish consumption has experienced a shift, from fresh (frozen) fish to live fish. The obstacles often faced by cultivators are death before the fish arrive at their destination, the cause of fish death is due to stress and physical damage due to mishandling. To avoid the high mortality rate of carp during the transportation process, fish entrepreneurs have begun to develop a dry transportation system, namely a system of transporting live fish using non-water transportation media. In the transportation of live fish without water media, the fish are made in a state of calm or stunning. Anesthesia can be done by giving an anesthetic in which the fish becomes unconscious during the transportation process. The advantage of stunning this fish is that it makes it easier to carry out the transportation process without water media, makes the fish not move much during the transportation process and minimizes the risk of fish being injured so as to allow a longer transportation time. One of the natural ingredients that can be used for anesthesia is tobacco (Nicotiana tabacum). The purpose of this study was to determine the effect of anesthetic tobacco extract (N. tobacum) on the hematological condition of carp (C. carpio) by dry transportation method. The treatments tested were soaking tobacco extract as fish anesthetic before transportation with different concentrations, namely, in treatment 1 (P1) without soaking tobacco extract, treatment 2 (P2) soaking tobacco extract 1 ml, treatment 3 (P3) soaking tobacco extract 2 ml, treatment (P4), soaking extract 3 ml. The results of this study that the use of tobacco leaf extract as an anesthetic in the dry transportation system causes hematological levels to increase and decrease but are still in normal levels, the best dose of tobacco extract is 1ml/L with a stunning speed of 917 minutes, recovery time is 239 minutes and has an SR value of 76%.